Using a gender lens to explore farmers’ adaptation options in the face of climate change: Results of a pilot study in Uganda - Kyazze, Florence Birungi; Owoyesigire B; Kristjanson, Patricia M.; Chaudhury M (2012)
Uganda, and especially the Rakai district, is highly vulnerable to climate variability and likely to be amongst the worst hit under climate change. Any responses to climate change affected communities cannot be considered complete unless women-specific responses are interwoven in a variety of adaptation options considered in the target area. The overall objective of this short-term research was to test tools and methodologies developed by CCAFS, FAO on analysis of gender issues in climate change, agriculture and food security. The study took place from the 1–4 November 2011, in the village of Kyengeza village in Uganda.